HARMONISASI AYAT AL-QUR’AN MELALUI METODE AL-JAM’U WA AL-TAUFIQ DAN NASKH : PENDEKATAN TAFSIR YANG KOMPREHENSIF - Azahro, Salma Aulia; Abdallillah , Najwa Aisyah; Muttaqin, Imamul (Relinesia: Jurnal Kajian Agama dan Multikulturalisme Indonesia, 2024)
This article investigates the complementary methods of al-Jam’u wa al-Taufiq (reconciliation and harmonization) and naskh (abrogation) within Qur’anic exegesis to address perceived contradictions in the Qur’anic text. As the central source of Islamic doctrine and law, the Qur’an presents verses that, at times, seem contradictory. Islamic scholars have historically employed al-Jam’u wa al-Taufiq to harmonize these verses by uncovering contextual consistencies and deeper unified meanings. Conversely, naskh is applied when reconciling verses appears untenable, suggesting that earlier rulings are superseded by later ones. This study explores the theoretical underpinnings and historical evolution of both methods, examining how they have been utilized by classical and contemporary scholars to maintain the coherence and integrity of the Qur’anic message. By analyzing specific case studies, the paper demonstrates the practical application of these methods and discusses their relevance in contemporary Islamic thought. The integration of al-Jam’u wa al-Taufiq and naskh provides a comprehensive framework for resolving interpretative challenges, ensuring that the Qur’anic text remains a consistent and authoritative guide for Muslims.